Prevalence of celiac disease in adult Chinese patients with diarrhea‐predominant irritable bowel syndrome: A prospective, controlled, cohort study. Issue 3 (16th April 2018) - Kou, Guan Jun; Guo, Jing; Zuo, Xiu Li; Li, Chang Qing; Liu, Chao; Ji, Rui; Liu, Han; Wang, Xiao; Li, Yan Qing
Abstract : Objective: Celiac disease is a chronic inflammatory enteropathy with a symptom spectrum similar to that of irritable bowel syndrome (IBS). It is a common but largely undiagnosed condition in the Western countries. However, it is extremely rare among Chinese individuals, and few studies have investigated its prevalence in China. The aim was to determine the prevalence of celiac disease in patients with IBS who were diagnosed using the Rome III criteria in a single center of northern China. Methods: This was a single‐center, prospective, controlled cohort study performed in Qilu Hospital involving 246 patients with IBS and 246 healthy controls. Blood samples were drawn to assess serum tissue transglutaminase immunoglobulin A (tTg‐IgA). Patients with a positive or equivocal tTg‐IgA (≥15 U/mL) were subjected to probe‐based confocal laser endomicroscopy (pCLE) and duodenal biopsy to confirm celiac disease. Results: Altogether 12 (4.9%) patients with IBS and two (0.8%) healthy controls were positive or equivocal for serum tTg‐IgA. Of these, five patients with IBS underwent pCLE and a targeted biopsy; all were histopathologically found to have celiac disease, although one was eventually diagnosed with lymphoma. After implementation of a gluten‐free diet, seven patients serologically positive for IBS showed clinical improvement, thus our study illustrated a minimum prevalence of 2.85% of celiac disease among patients with IBS in our center. Conclusions: Celiac disease is not rare in Chinese individuals, particularly among those with IBS. Therefore, it should receive higher attention in clinical practice in China.